Mode converter between channel waveguide and slot waveguide - Zhang, Jing (2013)
Silicon slot waveguide based mode converter was designed for the effective mode conversion and polarization rotation between a horizontal channel waveguide and a vertical slot waveguide. The device with minimum length of 40μm was demonstrated in amorphous silicon waveguides to provide the mode conversion between the TE mode in the horizontal channel waveguide and the TM mode in the horizontal slot-waveguide. The insertion loss at the transition region plus the propagation loss in 1.5mm long slot waveguide was less than 3dB. More than 10 dB polarization extinction ratio (PER) was achieved in this device.